Inclusive Education Training For Teachers To Improve Literacy And Student Character In Juniorhigh School - Trisman Harefa; Riswan Zega; Silvan Herniyanti Telaumbanua (Bhinneka Publishing, 2026)
The integration of digital technology in education has become an essential strategy for improving teaching quality and learning outcomes. However, many schools still experience challenges in utilizing digital learning tools effectively. This community service program aimed to improve students’ English pronunciation skills and enhance teachers’ competence in managing digital learning materials through technology. The program was conducted at UPTD SMP Negeri 4 Gunungsitoli Selatan and involved students and teachers as participants. The implementation consisted of observation, coordination, training activities, evaluation, and mentoring. Students received training on the use of the Elsa Speak application to improve pronunciation, while teachers were trained to use Google Site as a digital learning platform. The results showed that students demonstrated high enthusiasm and increased confidence in practicing English pronunciation. Teachers also showed positive responses to the use of Google Site for organizing and distributing learning materials. These findings indicate that digital-based training can support inclusive learning environments and improve both student engagement and teacher digital competence. Continuous digital training is recommended to strengthen technology integration in schools.